2015
DOI: 10.1159/000402936
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Receptor Radionuclide Therapy of Neuroendocrine Tumors

Abstract: Peptide receptor radionuclide therapy (PRRT) has been a well-accepted and effective therapeutic modality for inoperable or metastatic gastroenteropancreatic, bronchopulmonary and other neuroendocrine tumors for almost 2 decades. In general, PRRT is well tolerated with moderate toxicity in the majority of patients if the necessary precautions, appropriate dosage and coadministration of amino acids are undertaken. The two most commonly used radiopeptides, (90)Y-octreotide and (177)Lu-octreotate, produce signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…The clinical responses for diarrhoea and flushing continued to improve during treatment with LAN and during the follow-up period supporting the notion of maintenance therapy with LAN following PRRT. The adverse events reported were also consistent with published data on the use of PRRT [ 8 , 27 29 ]. Most patients (52.2%) in the GEP-NET FAS group received a LAN dosage of 120 mg every 28 days.…”
Section: Discussionsupporting
confidence: 88%
“…The clinical responses for diarrhoea and flushing continued to improve during treatment with LAN and during the follow-up period supporting the notion of maintenance therapy with LAN following PRRT. The adverse events reported were also consistent with published data on the use of PRRT [ 8 , 27 29 ]. Most patients (52.2%) in the GEP-NET FAS group received a LAN dosage of 120 mg every 28 days.…”
Section: Discussionsupporting
confidence: 88%
“…Mild adverse events resulting from this type of therapy include nausea, vomiting, fatigue, fever, and diarrhea [6]. Greater hematological and renal toxicities have been also reported, particularly with 90 Y-DOTATOC versus 177 Lu-DOTATATE [16]. While most symptoms are described as manageable, several studies have shown resultant myelodysplastic syndrome, acute leukemia, or other cancers, which have also been reported in other standard of care radiotherapies, such as with 131 I-MIBG [13,[16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Greater hematological and renal toxicities have been also reported, particularly with 90 Y-DOTATOC versus 177 Lu-DOTATATE [16]. While most symptoms are described as manageable, several studies have shown resultant myelodysplastic syndrome, acute leukemia, or other cancers, which have also been reported in other standard of care radiotherapies, such as with 131 I-MIBG [13,[16][17][18][19][20][21]. Here, we show two cases where the patients received either 177 Lu/ 90 Y-DOTATOC or 177 Lu-DOTATATE and demonstrated remarkable response rates with almost complete resolution of several foci.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lutetium-177 therefore provides excellent properties both for RIT and immuno-SPECT-imaging of small solid tumors or metastatic lesions even at an early stage of the disease. A number of 177 Lu-labeled radiopharmaceuticals such as the somatostatin analogues 177 Lu-DOTATOC/DOTATATE have already demonstrated the great potential of 177 Lu-based endoradiotherapy (Bodei et al 2015;Demirci et al 2018;Forrer et al 2005;Kasi et al 2019). Nevertheless, both radiometals 90 Y and 177 Lu are typical candidates for mAb-based applications.…”
Section: Introductionmentioning
confidence: 99%